El valor probatorio de las actas de inspección - Tirado Barrera, José Antonio (2021)
The evidentiary value of the inspection reports is one of the most relevant aspects of the legal treatment of the administrative activity of inspection or control, insofar as it usually constitutes an essential evidentiary means for the determination of the responsibilities of the audited parties. In this sense, it is important to take into account the discussion on the determination of the scope of the presumption of certainty of the inspection reports as opposed to the presumption of innocence of the persons being inspected, among other aspects.